A Javanese Spirituality in the Poem Risalah Tamba Ngantuk by KH. Mohammad Zuhri: Javanese Spirituality in the Poem Risalah Tamba Ngantuk by KH. Mohammad Zuhri - Hana Mufti Auliya Masbakah; Yusro Edy Nugroho; Rahma Ari Widihastuti (Kawruh: Journal of Language Education, Literature and Local Culture, 2025)
This article examines the spirituality of the Javanese people as reflected in Syair Risalah Tamba Ngantuk, a work by KH. Mohammad Zuhri that conveys strong moral and religious messages. The syair represents Javanese Islamic teachings through self-awareness, repentance, and a personal relationship with God. This study aims to reveal the forms, expressions, and meanings of spirituality in the syair using Puspoprojo’s hermeneutical approach, which consists of three principles: grammatical (nalar rasa), historical (pangerten kontekstual), and philosophical (laku tafsir). Using a qualitative method with thematic content analysis, the study finds that spirituality in the syair is expressed through teachings on the awareness of death, the importance of repentance, ethics in seeking knowledge, cosmological views of the soul, and prayer as a spiritual act. The hermeneutic interpretation shows that KH. Mohammad Zuhri not only delivers normative Islamic teachings but also expresses spiritual values in a gentle, poetic, and contextual language. Thus, Syair Risalah Tamba Ngantuk embodies a creative dialogue between Islam and Javanese culture, remaining relevant to contemporary religious life.